Murder on the highway : the Viola Liuzzo story - Siegel, Beatrice (Four Winds Press ; Maxwell Macmillan Canada ; Maxwell Macmillan International, 1993)
Presents the life of the civil rights worker who was murdered shortly after the 1965 march from Selma to Montgomery, Alabama, and discusses the rights of Afro-Americans living in the South prior to and following her death.